Aneurysm-related ischemic ventricular tachycardia: safety and efficacy of catheter ablation. Issue 13 (March 2017) - Guo, Jin-Rui; Zheng, Li-Hui; Wu, Ling-Min; Ding, Li-Gang; Yao, Yan
Abstract : Abstract: Left ventricular aneurysm (LVA) postmyocardial infarction (MI) might be an arrhythmogenic substrate. We examined the safety and efficacy of catheter ablation of LVA-related ventricular tachycardia (VT). Thirty-three consecutive patients who underwent primary catheter ablation of ischemic VT were divided into LVA group (11 patients, mean age 61.9 years, 10 men) and none LVA group. Acute procedural outcomes, complications, and long-term outcomes were assessed. In LVA group, average number of induced VTs were 3.2 ± 2.6 (range 1–7), clinical VTs were located in the ventricular septum scar zone in 4 (36.4%) patients, acute success was achieved in 7 (63.6%) patients, partial success in 3 (27.3%) and failure in 1 patient, while none LVA group showing a statistically similar distribution of acute procedural outcomes ( P = 0.52). There were no major or life-threatening complications. VT-free survival rate at median 19 (1–44) months follow-up was numerically but not significantly lower in LVA versus none LVA group (48.5% vs 62.8%, log-rank P = 0.40). Catheter ablation of ischemic VT in the presence of LVA appears feasible and effective, with about one-third of cases having septal ablation targets. Further studies are warranted.